Cross-Cultural Communication and Organizational Culture in Forming Organizational Cohesiveness - Simanullang*, Fryandi; Roem, Elva Ronaning; Arif, Ernita (Universitas Syiah Kuala, 2024)
An organization, in achieving its goals, is propelled by the individuals within it who act as members of the organization. Members of the organization engage in coordination and collaboration, all of which require communication. An organization may consist of a group of people with cultural differences. Cultural differences need to be managed effectively to avoid barriers among members. One form of management is reflected in the members' ability to engage in cross-cultural communication competence. Additionally, organizational culture is a crucial element in shaping a shared meaning system. The integration of all organization members is necessary in achieving organizational goals, especially in situations where there are cultural background differences among members. Cultural differences influence the interpretation and perception processes of organizational members regarding messages and information that arise in the communication process. A cohesive organization is an aspiration that needs to be realized through efforts to strengthen organizational culture and enhance cross-cultural communication competence among all organization members. Cohesiveness represents how organization members are not separated by barriers arising from cultural background differences. This research employs a qualitative method with data collection through document studies. The aim of this study is to uncover the reasons why cross-cultural communication competence and organizational culture are crucial in building cohesiveness within an organization. The researcher conducting this study received funding from the Domestic Master's Scholarship Program of the Ministry of Communication and Information Technology.